دراسة تحليلية لواقع المؤسسة العامة السورية للتأمين - عكروش, محمد; دريباتي, يسيرة; جلمودي, دارين محمد (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يتناول البحث دراسة تحليلية لواقع المؤسسة العامة السورية للتأمين بوصفها واحدة من مؤسسات التامين العاملة في سوق التأمين السورية إلى جانب المؤسسة العامة للتأمينات الاجتماعية و المؤسسة العامة للتأمين و المعاشات ,حيث تم التعرف على آلية عمل هذه المؤسسة ومدى تأثيرها في النشاط الاقتصادي في سورية من خلال الاحتياطيات المتكونة في صندوق هذه المؤسسة عن طريق استثمارها بالشكل الذي يحقق النفع العام للمجتمع على كافة الأصعدة ، كما تم حساب الفجوة التأمينية بهدف إجراء تقدير مستقبلي لمعرفة نقاط القوة و الضعف في نشاط المؤسسة , وفي النهاية تم التوصل من خلال دراستنا إلى نتائج عدة أهمها تذبذب في قيم إيرادات ونفقات واحتياطيات المؤسسة خلال فترة الدراسة, كذلك وجود أثر واضح وملموس لهذه المؤسسة في النشاط الاقتصادي بشكل عام من خلال الاحتياطيات المتكونة في صندوقها والقيم المستقبلية المتوقَّعة للاحتياطيات والتي تتزايد بشكل أسي, الأمر الذي يؤكد استمرار المؤسسة العامة السورية للتأمين بحيازة الحصة الأكبر في سوق التأمين السورية . The research deals An Analytic study for the factual of the Syrian public firm of insurance as one of the firms which work in the Syrian insurance market with the public firm for social security and the public firm of insurance and livelihood for this we recognized from our research the job of this firm and its effect on economic activity in Syria from reserves which would be formed in the fund of this firm ,by investing it in the form that realize general profit at all scenes ,so we calculated the insurance gape for making a future estimation for learning the weaknesses and strength issues in the activity of the firm, at the end our previous study concluded several results the most important of them is an oscillation that happened in the changes which happened in the values of revenues and expenses during the period of our study, and showed occurrence a felt and clear effect on the social development process from the reserves which formed in the fund of the firm, and the expected futurism values of the reserves which grow with exponential form, that emphasize the continuity of the Syrian public firm of insurance in possessing the greatest share in the Syrian insurance market.